Construction of SARS-CoV-2 Virus-Like Particles by Mammalian Expression System - Xu, Ruodan; Shi, Mingfei; Li, Jing; Song, Ping; Li, Ning (Frontiers in Bioengineering and Biotechnology, 2020)
Virus-like particle (VLP) is a self-assembled nanostructure incorporating key viral structural proteins. VLP resembles molecular and morphological features of authentic viruses but is non-infectious and non-replicating due to lack of genetic materials. Successful applications of VLP has been shown in vaccinological and virological research. As an accessibly safe and relevant substitute of naturally pathogenic viruses, the construction of SARS-CoV-2 VLPs is much in demand in the ongoing fight against 2019 Coronavirus disease (COVID-19) pandemics. In the current study, using mammalian expression system, which is advantageous in maintaining correct protein glycosylation patterns, we efficiently constructed SARS-CoV-2 VLPs. We showed that among four SARS-CoV-2 structural proteins, expression of membrane protein (M) and small envelope protein (E) are essential for efficient formation and release of SARS-CoV-2 VLPs. Moreover, the corona-like structure presented in SARS-CoV-2 VLPs from Vero E6 cells is more stable and unified, as compared to those from HEK-293T cells. Our data demonstrate that SARS-CoV-2 VLPs possess molecular and morphological properties of native virion particles, which endow such VLPs with a promising vaccine candidate and a powerful tool for the research of SARS-CoV-2.